Secular Trends in Anthropometric Characteristics and Health-Related Physical Fitness in Macedonian Children: the Makfit Studies - Elezi, Abdulla; Elezi, Gresa; Gontarev, Seryozha; Georgiev, Georgi (LLC OVS, 2021)
The purpose of the present study was to analyze the secular trends in anthropometric characteristics and health-related physical fitness (i.e., flexibility, muscular strength and speed/agility) in Macedonian children between 2012 and 2019. Materials and methods. We analyzed the secular trends in anthropometric characteristics and health-related physical fitness in Macedonian children between 2012 and 2019. Two representative population studies were conducted 7 years apart in children (6-10 years) from Skopje (Mаcedonia). Both studies used the same anthropometric measures and tests to assess physical fitness: height, weight, body mass index, body fat percentage, muscle mass percentage, sit and reach, handgrip strength, standing long jump, 30 sec sit ups, and 4 × 10 m shuttle run.  Result. The boys and girls measured in 2019 had significantly better performance in the sit and reach (Cohen’s d ~0.4 and ~0.5, respectively), 30 sec sit ups (Cohen’s d ~0.3 and ~0.2, respectively), and 4 × 10 m shuttle run (Cohen’s d ~0.7 and ~0.8, respectively) tests compared to those measured in 2012–2013. Levels of the standing long jump were significantly lower in 2019 in boys and girls (Cohen’s d ~0.6 for both).  Conclusions. Based on the results of the study, it can be concluded that Macedonian children measured in 2019 have higher levels of flexibility, abdominal muscle strength and coordination, speed and agility, but lower levels of explosive force of the lower limbs than their counterparts measured. 7 years ago, no statistically significant differences were found in anthropometric measures and measures of body weight.